Conceptualizing Consumer Body Awareness - Padhaiskaya, Tatsiana; Weijo, Henri A (Journal of Consumer Research, 2026)
Abstract Existing research typically treats body awareness as a subset of self-awareness, which emphasizes identity and appearance at the expense of embodied sensations. This article offers a corrective by reconceptualizing consumer body awareness as a distinct, cultivated capacity, defined as the ability to notice, make sense of, and respond to exteroceptive, proprioceptive, and interoceptive sensations with the help of marketplace resources. Prior studies show that consumers are increasingly turning to the marketplace to find bodily reconnection and seek relief from the disembodied pull of digitalized, market-mediated life. Research also shows that although marketplace resources can help build body awareness, they can also distract from it. What the literature does not explain is how consumers engage with marketplace resources as their body awareness evolves. Building on an ethnographic inquiry into ultra-running, this article introduces a four-stage process of cultivating consumer body awareness: attuning, listening, connecting, and integrating. Findings show how marketplace resources both enable and obstruct body learning across these stages, ultimately recalibrating consumption choices and brand relationships.